2017
DOI: 10.1177/107327481702400118
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Dissemination and Neoplastic Meningitis in Primary Brain Tumors

Abstract: Background: Neoplastic meningitis, also known as leptomeningeal disease, affects the entire neuraxis. The clinical manifestations of the disease may affect the cranial nerves, cerebral hemispheres, or the spine. Because of the extent of disease involvement, treatment options and disease staging should involve all compartments of the cerebrospinal fluid (CSF) and subarachnoid space. Few studies of patients with primary brain tumors have specifically addressed treatment for the secondary complication of neoplast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 195 publications
(524 reference statements)
0
4
0
Order By: Relevance
“…In our study we did not find any case of primary brain tumor with metastasis to CSF. However, other studies[ 19 20 ] have seen a predominance (86%) of pediatric brain tumors with metastasis to CSF.…”
Section: Discussionmentioning
confidence: 95%
“…In our study we did not find any case of primary brain tumor with metastasis to CSF. However, other studies[ 19 20 ] have seen a predominance (86%) of pediatric brain tumors with metastasis to CSF.…”
Section: Discussionmentioning
confidence: 95%
“…The research a s s i s t e d t o re p re s e n t t h a t p ro p e n s i t y o f dissemination of these tumors through CSF by BNCT had increased. A review that was performed on neoplastic meningitis and cerebrospinal fluid dissemination in primary brain tumors showed that CSF cytology results in neoplastic meningitis' therapeutical response [17]. The study indicates that the survival rates of the tumor patients after the central nervous system directed therapy differs depending on the primary conditions and that there is a need of new method adoption for the optimal treatment neoplastic meningitis, as it has been poorly explained.…”
Section: Literature Reviewmentioning
confidence: 99%
“…7 Furthermore, NM is diagnosed in 1-2% of patients with primary brain tumors, such as ependymomas, medulloblastomas, germinomas and gliomas. 8 In more than 70% of patients NM develops in the setting of an active systemic disease, while in 20% of patients it occurs in association with a stable disease, and in up to 10% of patients it is the first manifestation of cancer. Some risk factors for developing NM have been recognized: concomitant brain metastases are associated with NM in 33-54% of patients with breast cancer, 56-82% with lung cancers and 87-96% with melanomas.…”
Section: Epidemiologymentioning
confidence: 99%